Risk assessment of drug-induced QT prolongation - Isbister, Geoffrey K (Aust Prescr, 2015)
Drugs can cause prolongation of the QT interval, alone or in combination, potentially leading to fatal arrhythmias such as torsades de pointes. When prescribing drugs that prolong the QT interval, the balance of benefit versus harm should always be considered. Readouts from automated ECG machines are unreliable. The QT interval should be measured manually. Changes in heart rate influence the absolute QT interval. Heart rate correction formulae are inaccurate, particularly for fast and slow heart rates. The QT nomogram, a plot of QT interval versus heart rate, can be used as a risk assessment tool to detect an abnormal QT interval.